Penerapan Metode Job Order Costing dalam Menentukan Harga Pokok Produksi pada Sistem Informasi Pengendalian Biaya - Permana, Denny Riandhita Arief (JATISI, 2024)
Abstract PT Ganding Toolsindo is one of the manufacturing companies that focused on the automotive sector with core business are manufacture of automotive component and engineering. In marketing their products, Marketing Division made quotation letter addressed to the customer. The problems that happened is quotation letter still done manually and there is hoarding of the old data so it resulting duplication. In the quoted letter stated the production cost to determine cost of goods manufactured and selling price, one of them is material costs. Material costs in PT Ganding Toolsindo are not controlled every time there is a price increase, even though it will have an effect on the high of production cost. The determination of the production cost at PT Ganding Toolsindo is still through manual calculations and there is no detailed cost classification. In order to overcome these problems, a cost control information system is needed in determining the cost of goods manufactured using the Job Order Costing method and using a database to make data and cost management easier. With this cost control information system, it can help the Marketing Division to identify the production costs of each order and prevent the increase in production costs incurred. Keywords—Cost Control, Cost of Goods Manufactured, Selling Price, Job Order Costing